Performance evaluation of crumb rubber and paraffin modified stone mastic asphalt - Kok, Baha Vural; Yilmaz, Mehmet; Akpolat, Mustafa (Canadian Science Publishing, Nrc Research Press, 2016)
Recently, crumb rubber (CR) obtained from waste tires and Fischer-Tropsch paraffin are mostly used in bitumen modification to improve the performance of bituminous mixtures. Each of these additives affects the different properties of mixtures. There are limited studies in the literature about the combined usage of additive in the same mixture to utilize the different characteristics. In this study, the stability, stiffness, fatigue resistance, permanent deformation resistance, and moisture susceptibility characteristics of the stone mastic asphalt prepared with the bitumen modified with CR and paraffin were examined and compared with the control mixture. It was determined that CR-modified mixtures showed significantly more elastic characteristics. The mixture in which the 10% CR and 3% paraffin were used together gave better results in terms of moisture susceptibility and fatigue resistance when compared with the control mixture. It was determined that the use of paraffin together with CR contributed to the improved performance, and was in accordance with the CR in terms of mechanical characteristics of stone mastic asphalt.
Keywords: crumb rubber; paraffin; stone mastic asphalt; mechanical properties